Study of Governement Efforts for Protection of Consumers in India - Garg, Ajay Kumar (Journal of Commerce and Trade, 2021)
Consumers, all over the world, want their value for money in the form of quality goods and better services in a real sense. Advances in technology and innovation will no doubt have a significant impact on the quality, accessibility, availability and security of goods and services; but the reality of life is that consumers are still the victims of abusive practices that have existed for many years. Consumer exploitation takes many forms such as adultery, fake drugs, questionable purchase plans, high prices, low quality, poor resources, deceptive advertisements, dangerous products, black marketing and more. The Consumer Protection Act aims to provide quick and easy redress for consumer complaints. This mechanism is authorized to provide limited time freedom to consumers. The growing interdependence of the global economy and the international environment of many business processes has contributed to the development of a global emphasis on the protection and promotion of consumer rights. Consumers, clients and customers around the world, want value for money in the form of quality goods and better services. Modern development has undoubtedly had a profound effect on the quality, availability and security of goods and services.